Switching power supplies A--Z - Maniktala, Sanjaya (EngineeringPro., 2012)
This book is the most comprehensive study available of the theoretical and practical aspects of controlling and measuring Electromagnetic Interference in switching power supplies, including input filter instability considerations. The new edition is thoroughly revised with six completely new chapters, while the existing EMI chapters are expanded to include many more step-by-step numerical examples and key derivations and EMI mitigation techniques. New topics cover the length and breadth of modern switching power conversion techniques, lucidly explained in simple but thorough terms, n.